123 A case of primary angiitis of central nervous system presenting with cerebral haemorrhage. Issue 6 (27th May 2022) - Chun, Strathan; Lee, Pei Ling; McClusky, Lauren; Appleton, Jason
Abstract : We report an interesting case of a previously fit and well 27-year-old man who initially presented with seizure to his local district general hospital. A series of investigations including a CT head, CT angiogram and a lumbar puncture were performed but no formal diagnosis was confirmed. He was discharged with a label of multifocal primary intracerebral haemorrhage of unknown aetiology. He was discharged to a Neurological Rehabilitation Unit where he was undergoing intensive rehabilitation. Twelve months later he represented to our regional neuroscience centre with status epilepticus char- acterised by multiple generalised tonic-clonic seizures and reduced level of consciousness. He required intensive care admission and was investigated extensively with multiple diagnostic techniques, including; a CT head, CT venogram, CT angiogram, MRI and a lumbar puncture. Following a long admission the diagnosis of PACNS was made with confirmatory positive histopathology findings. Unfortunately, the pre-existing neurological deficits and functional disabilities are likely to persist indefi- nitely. The patient was managed with immunosuppressant to reduce recurrence of disease aiming to prevent further decline. dinochun@hotmail.com